Proceedings 20th IEEE International Parallel &Amp; Distributed Processing Symposium 2006
DOI: 10.1109/ipdps.2006.1639484
|View full text |Cite
|
Sign up to set email alerts
|

Design space exploration for low-power reconfigurable fabrics

Abstract: Abstract-This paper presents a parameterizable, coarsegrained, reconfigurable fabric model that attempts to maintain Field Programmable Gate Array (FPGA)-like programmability and Computer Aided Design (CAD), with Application Specific Integrated Circuit (ASIC)-like power characteristics for Digital Signal Processing (DSP) style applications. Using this model, architectural design space decisions are explored in order to define an energy-efficient fabric. The impact on energy and performance due to the variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In paper [45], Gayatri Mehta, et.al, proposed a reconfigurable fabric models for maintain FPGAs. The authors concluded that the feature called reconfigurable is like a reprogrammable; that could be used for reducing area requirement.…”
Section: Related Workmentioning
confidence: 99%
“…In paper [45], Gayatri Mehta, et.al, proposed a reconfigurable fabric models for maintain FPGAs. The authors concluded that the feature called reconfigurable is like a reprogrammable; that could be used for reducing area requirement.…”
Section: Related Workmentioning
confidence: 99%
“…In our previous research, we studied the impact of varying different design parameters such as the h of the functional units, homogeneous vs. heterogeneous functional units, various functional unit implementation techniques, granularity of the interconnect, interconnect patterns, tical routing onto physical characteristics like power, performance, and area [5,25,8,9]. We attempted to minimize the cardinality of the interconnect and the number of operations supported by each ALU, and maximize the use of dedicated pass gates in the fabri all of the optimizations a very large number of ALUs as pass remain and results appear to be area-inefficient, which motivates the idea of exploring alternative approaches in this paper.…”
Section: Domain Specific Fabricmentioning
confidence: 99%
“…Stripe-based fabrics in particular (e.g., see Figure 2) are quite promising due to their good fit to a data flow graph structure [5,25,8,9]. When a data flow graph is mapped to a stripe-style structure, however, data dependency edges often traverse multiple rows.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our initial design space exploration studies, a 4:1 interconnect was selected to create enough flexibility in the routing while reducing power consumption and delay in the fabric [12,13]. An example of this interconnection is shown in Figure 3.…”
Section: Benchmark Driven Interconnectmentioning
confidence: 99%